2014
DOI: 10.1007/s10048-014-0421-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the novel nuclear-encoded mitochondrial protein CHCHD10 in a family with autosomal dominant mitochondrial myopathy

Abstract: Mitochondrial myopathies belong to a larger group of systemic diseases caused by morphological or biochemical abnormalities of mitochondria. Mitochondrial disorders can be caused by mutations in either the mitochondrial or the nuclear genome. Only 5% of all mitochondrial disorders are autosomal dominant. We analyzed DNA from members of a previously reported Puerto Rican kindred with an autosomal dominant mitochondrial myopathy (Heimann-Patterson et al. 1997). Linkage analysis suggested a putative locus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 25 publications
11
81
0
Order By: Relevance
“…Several studies have characterized the effects of CHCHD10 by analyzing these mutations in skin fibroblasts from patients (14,9,20) or by overexpression of these mutations in WT cells (8,37). Here we show that CHCHD10 plays a key role in the regulation of electron transport chain function in the mitochondria as well as a novel role in the nucleus as a transcriptional repressor at the ORE. We selected two CHCHD10 mutations -P80L and G66V -for detailed study.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Several studies have characterized the effects of CHCHD10 by analyzing these mutations in skin fibroblasts from patients (14,9,20) or by overexpression of these mutations in WT cells (8,37). Here we show that CHCHD10 plays a key role in the regulation of electron transport chain function in the mitochondria as well as a novel role in the nucleus as a transcriptional repressor at the ORE. We selected two CHCHD10 mutations -P80L and G66V -for detailed study.…”
Section: Discussionmentioning
confidence: 62%
“…Little is known, however, about the physiological role of CHCHD10 (7). Most studies have focused on characterizing CHCHD10's effects in mitochondria by testing the effects of pathogenic mutations in a cell culture system (8,9,14). These studies have suggested that CHCHD10 affects stability of mitochondrial cristae (9, 14), COX activity (7), formation of mitochondrial networks (8), stability of mitochondrial DNA, and apoptosis (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in CHCHD10 may disrupt the morphology of mitochondrial cristae, affect the stability of mitochondrial DNA, induce mitochondrial fragmentation, and reduce mitochondrial complex-IV activities Ajroud-Driss et al, 2015). Two novel variants identified in the current study, p.A35D and p.P23T, affect amino acids in the non-structured N-terminal region of CHCHD10 protein.…”
mentioning
confidence: 69%
“…Affected family members were presented with a complex phenotype that included symptoms of amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), cerebellar ataxia, Parkinson's disease and a mitochondrial myopathy associated with multiple mitochondrial DNA deletions. So far, seven missense CHCHD10 mutations have been reported in patients with a broad phenotypic range, including ALS/FTLD (p.S59L and p.P34S) Chaussenot et al, 2014), ALS (p.R15L and p.G66V) (Johnson et al, 2014;Muller et al, 2014), myopathy (p.R15S and p.G58R) (Ajroud-Driss et al, 2015) and lateonset spinal motor neuronopathy (p.G66V) (Penttila et al, 2015). All of them affect exon 2 (a mutational hotspot of CHCHD10).…”
mentioning
confidence: 99%